FOREIGN EXPERIENCE OF THE IMPLEMENTATION OF CERTAIN ELEMENTS OF TRANSITIONAL JUSTICE IN THE CONTEXT OF CRIMINOLOGY SECURITY OF DEOCCUPATION OF THE TERRITORY OF UKRAINE (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the study of certain elements of transitional justice of the post-war period used by foreign states to overcome the consequences of conflicts and committed offences in order to achieve reconciliation in society and prevent recurrence of conflicts and offences in the future. In the context of the issue of bringing perpetrators to justice, the author analyses the experience of overcoming the consequences of the military dictatorship of Argentina, in which one of the leading roles on the path to reconciliation is assigned to Argentine society. The analysis of the Bosnian experience shows that early transitional justice measures with the participation of international organisations took place during the war. Reparations for victims of conflict as a component of transitional justice are considered on the basis of the experience of the Republic of Chile, which has successfully used a wide range of reparation measures for various categories of persons recognised as victims of offences. Based on the analysis of international experience in the application of certain elements of transitional justice, the author outlines the risks and prospects for the Ukrainian transitional justice scenario.
Keywords: transitional justice; international experience; responsibility; victims; reparations